Assessment of maintenance strategies adopted by teachers and technologists for maintenance of workshop equipment in technical colleges of Taraba State, Nigeria - Wada, Zira B.; Adamu, Umar Kwami (Kashere Journal of Education, 2023)
The study was designed to assess the maintenance strategies adopted by the teachers for the maintenance of workshop equipment in Technical Colleges in Taraba state, Nigeria. A descriptive survey research design was used for the study. The study was carried out in all the 9 technical colleges in Taraba State. The study’s population included the teachers and workshop technologists from Taraba State’s nine technical colleges.35 teachers and 35 school workshop technologists were sampled for the study making total of 70 respondents. The instrument for data collection was Assessment of Maintenance Strategies Adopted by the Teachers and Technologists for the Maintenance of Workshop Equipment in Technical Colleges questionnaire. The questionnaire was validated and pilot tested. Cronbach Alpha method was used to test the reliability, and a 0.87 reliability coefficient was found. Two research questions and one hypothesis were raised to guide the study. The research questions were analysed using mean and standard deviation, while the hypothesis was tested using z-test statistics. The findings of the study revealed that most of the standard maintenance strategies were not adopted for maintenance of technical colleges workshop equipment in Taraba State. It was therefore recommended that the schools should be encouraged to adopt the appropriate maintenance strategies to safeguard and prolong the lives of the workshop equipment and its users.